Near maximum likelihood detection schemes for wireless MIMO systems. - Ho-Yin Fan, J. (IEEE Transactions on wireless communications)
In this letter, we propose two near maximum-likelihood detection (MLD) schemes for multiple input-multiple output antenna systems over flat fading channels. The schemes are based on utilizing an initial estimate of the received symbol and improving it by selectively updating various bits within the symbol. Simulation results show that the performance of the proposed schemes can approach that of MLD but with a significant reduction in complexity.